The Gospel Accoding to Jesus What is Authentic Faith? - MacArthur, John (Grand Rapids Zondervan Publishing House, 1988)
MacArthur looks at the condition of the "church" today and sees weak churches, many conversions and much enrollment that has less and less impact on our world today. He tackles issues such as: 1. there is no justification without regeneration. 2. Faith wi
Keywords: Theology - doctrine. Jesus Christ -- Person and offices. Christian life. Jesus Christ. Christology